A deletion causing NF2 exon 9 skipping is associated with familial autosomal dominant intramedullary ependymoma. Issue 2 (18th December 2013) - Zemmoura, Ilyess; Vourc'h, Patrick; Paubel, Agathe; Parfait, Béatrice; Cohen, Joëlle; Bilan, Frédéric; Kitzis, Alain; Rousselot, Cécilia; Parker, Fabrice; François, Patrick; Andres, Christian R.
Abstract: Background: Intramedullary ependymomas are rare and benign tumors in the adult. Little is known about their physiopathology, but the implication of the NF2 gene is suspected because of their presence in a third of patients with type 2 neurofibromatosis (NF2), a disorder caused by mutation of the NF2 gene. Methods: We conducted a clinical and genetic study of a family in which 5 of 9 members suffered from intramedullary ependymoma. Karyotyping and CGH array analysis were performed on DNA from peripheral blood lymphocytes from affected participants. The NF2 gene sequences were then determined in DNA from 3 nonaffected and all 5 affected members of the family. Results: Karyotype and CGH array findings were normal. Sequencing of NF2 revealed a heterozygous deletion, c.811-39_841del69bp, at the intron 8/exon 9 junction, in all affected members that was absent from all nonaffected members. RT-PCR analysis and sequencing revealed a novel NF2 transcript characterized by a skipping of exon 9 (75 bp). This deletion is predicted to result in a 25-amino acid deletion in the N-terminal FERM domain of neurofibromin 2. Modeling of this mutant domain suggests possible disorganization of the subdomain C. Conclusion: We report the first family with an NF2 mutation associated with intramedullary ependymomas without other features of NF2 syndrome. This mutation, which has not been described previously, may particularly affect the function of neurofibromin 2 in ependymocytes leading to the development of intramedullary WHO grade II ependymomas. We propose that sporadic intramedullary ependymomas should also be analyzed for this region of NF2 gene.